Characterization and properties of recycled polypropylene (rPP)/ recycled high density polythylene (rHDPE) blends and its composites - Siti Mariam Atiqah, Abdul Aziz (Universiti Malaysia Perlis (UniMAP), 2015)
Master of Science in Materials Engineering